Security architect : careers in IT service management - Collins, J. D. (Jon D.) (BCS guides to IT roles, 2014)
"Security architects are responsible for maintaining the security of an organisation's computer systems as well as designing, developing and reviewing security architectures that fit business requirements, mitigate risk and conform to security policies. They ensure that each unique set of security needs is addressed, that systems are protected and beneficial security change is implemented. The book provides practical, effective guidance for anyone looking to become a security architect or wanting to know more about what the role entails. It covers areas such as required skills, responsibilities, dependencies and career progression as well as relevant tools, standards and frameworks."--